Somatosensory Amplification, Anxiety, and Depression in Patients With Hepatitis B: Impact on Functionality. Issue 21 (May 2016) - Yilmaz, Ahmet; Ucmak, Feyzullah; Dönmezdil, Süleyman; Kaya, Mehmet Cemal; Tekin, Recep; Günes, Mehmet; Arslan, Necmi; Bulut, Mahmut
Abstract : Abstract: In the present study, we aimed to determine the differences in body image along with anxiety and depression levels, and also to evaluate their impact on disability parameters in patients with hepatitis B. Our study comprised 77 patients with hepatitis B (n = 41, chronic active patients; n = 36, patients with inactive hepatitis B) and 53 healthy individuals (control group). Enrolled patients responded to several questionnaires, including a sociodemographic form, Sheehan Disability Scale (SDS), Hospital Anxiety and Depression Scale (HADS), and Somatosensory Amplification Scale. Patients with chronic active hepatitis B (CAHB) had higher levels of somatosensory perception than patients with inactive hepatitis B (IHB) and control group ( P < 0.001, P = 0.001, respectively). Patients with CAHB had high scores on all the 3 domains of SDS (work/school, P < 0.001; social life, P < 0.001; and family life, P < 0.001). Also, patients with CAHB had a significantly higher HADS total score, HADS anxiety score, and HADS depression score than control group ( P < 0.001, P < 0.001, P < 0.001, respectively). No significant difference was noted between patients with CAHB and patients with IHB with regard to HADS depression score; however, HADS anxiety and HADS total scores were significantly higher in the CAHB group (NS, P = 0.027, P = 0.035, respectively). Moreover, the IHB group exhibited higher scores for the work/school and social life domains of SDS than those of the control group ( P = 0.008, P = 0.047). Although patients with CAHB may present with somatosensory amplification, anxiety, and depression, patients with IHB do not exhibit such symptoms. However, functionality is affected in both carrier and active patient groups. We believe that routine health checks of patients with hepatitis B should include psychiatric evaluation, psychiatric examination, and follow-up.